Carbonation of geopolymer concrete at different depth effect - Siti Noor Baizura Binti Sulaiman (School of Environmental Engineering, University Malaysia Perlis, 2014)
Since admixtures for cement are known to enhance the properties of cement and by implication expand the quality of cement.. The Ordinary Portland Cement used as a primary binder in the concrete. Application of concrete for building structures and infrastructure can contribute to the emission of carbon dioxide. The geopolymer concrete has been introduced to substantially curb carbon dioxide emission. The geopolymer concrete currently used for disposal of coal combustion products and surface bodies of fresh water by eliminating fly ash and palm oil fuel ash (POFA) disposal sites.